2022
DOI: 10.3389/fonc.2022.904258
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxyisovaleryl-Shikonin Exerts an Antitumor Effect on Pancreatic Cancer Through the PI3K/AKT Signaling Pathway

Abstract: Pancreatic cancer (PC) is marked with a low survival rate and lack of recognized effective treatment strategy. We investigated the antitumor effect of β-hydroxyisovaleryl-shikonin (β-HIVS) on PC and the associated working mechanism. Cell toxicity was determined using Cell Counting Kit-8 (CCK-8) assay. Acridine Orange/Ethidium Bromide (AO/EB) double-fluorescent staining assay accompanied by flow cytometry was utilized to estimate cell apoptosis. Cell cycle, reactive oxygen species (ROS), and mitochondrial membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Cytotoxicity analysis revealed that Sanguinarine chloride and (R)-Shikonin had considerable toxic effects for all doses and incubation times tested. These findings are consistent with previous reports of these compounds’ high cytotoxicity in several cancer cell lines, supporting their possible use as antitumoral drugs [ 30 , 31 , 32 , 64 ]. On the other hand, Fisetin, Honokiol, Tanshinone IIA, and α-Mangostin were well-tolerated at doses of 5 or 10 μM in the tested cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Cytotoxicity analysis revealed that Sanguinarine chloride and (R)-Shikonin had considerable toxic effects for all doses and incubation times tested. These findings are consistent with previous reports of these compounds’ high cytotoxicity in several cancer cell lines, supporting their possible use as antitumoral drugs [ 30 , 31 , 32 , 64 ]. On the other hand, Fisetin, Honokiol, Tanshinone IIA, and α-Mangostin were well-tolerated at doses of 5 or 10 μM in the tested cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Cytotoxicity analysis revealed that Sanguinarine chloride and (R)-Shikonin had considerable toxic effects for all doses and incubation times tested. These findings are consistent with previous reports of these compounds’ high cytotoxicity in several cancer cell lines, supporting their possible use as antitumoral drugs [30-32,64]. On the other hand, Fisetin, Honokiol, Tanshinone IIA and α-Mangostin were well-tolerated at doses of 5 or 10 μM in the tested cell lines.…”
Section: Discusionsupporting
confidence: 92%
“…One point we should note is that β-HIVS might also exert anticancer effects through the inhibition of tyrosine kinases such as v-Src, EGFR, or VEGFR2 [10,17]. PI3K/AKT signaling has also been reported as a signal involved in the inhibitory effect on tumor growth of β-HIVS [18,19]. Thus, future studies are required to investigate if the effect of β-HIVS on tumor growth inhibition with reduced EpCAM expression depends on the reduction in dUTPase alone.…”
Section: Discussionmentioning
confidence: 99%